Perancangan Sistem Informasi Pemesanan Barbershop Berbasis Web - Sitanggang, Alfina Tiur Mida; Suryani, Ade; Hamdi, Raspan; ., Sunarsih; ., Arifin; Fatimah, Putri (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
The main problem often faced by barbershop businesses is the manual booking process, such as through phone calls or direct visits. This leads to long queues, scheduling errors, and inefficiency in customer data management. This study aims to design and develop a web-based barbershop booking information system that facilitates customers in making reservations and assists barbershop staff in managing service schedules effectively. The software development method used is the Waterfall model, which consists of requirement analysis, system design, implementation, testing, and maintenance stages. The analysis technique used is PIECES, aimed at identifying weaknesses in the old system and formulating the needs of the new system. The result of this study is a web-based booking information system that provides features such as user registration, service and barber selection based on time, schedule management, and automatic notifications. Black Box testing showed that all system functions work as expected. The system successfully reduced queues by up to 70% during a three-day operational simulation and improved service efficiency at the barbershop.